Surgical Outcomes of Concurrent Intraperitoneal Onlay Meshplasty and Laparoscopic Cholecystectomy: A Retrospective Observational Study - Prachi Praveen Agrawal; Abhijit S Joshi (Journal of Clinical and Diagnostic Research)
Introduction: Laparoscopic Cholecystectomy (LC) and Intraperitoneal Onlay Meshplasty (IPOM) have established themselves as standard and popular surgeries for gallstone disease and ventral hernia, respectively. However, their concurrent performance for co-existing gallstone disease and ventral hernia has never been studied. Aim: To determine the outcomes of the concurrent performance of LC and IPOM in patients with co-existing gallstone disease and ventral hernia. Materials and Methods: This retrospective observational study was conducted at the Department of General and Laparoscopic Surgery, Dr. L H Hiranandani Hospital, Mumbai, India from August 2005 to July 2024. Over 19 years, 15 patients with coexisting gallstone disease and ventral hernia (primary/recurrent) were operated upon in a single sitting. The following outcomes were studied: duration of surgery, intra and postoperative complications including mesh infection, duration of hospital stay, recurrence of hernia, time taken to resume normal activity, and cost of treatment. Proportions, percentages, and means were calculated. Results: The mean age of the patients was 55±12.36 years (range 35-77 years). The average duration of surgery was 62 minutes (range 48-70 minutes). There was no conversion to open surgery. The mean postoperative stay was 2.5 days. Total 3 (20%) patients developed seromas, which were identified on day 10. All three seromas were small in size, managed conservatively, and resolved by six weeks. No patient experienced any significant intra- or postoperative haemorrhage. There was no superficial or deep surgical site infection, and there was not a single case of mesh infection. There was no recurrence of the hernia. Patients resumed normal activity in an average of seven days. The total cost of concurrent treatment for both conditions was reduced by 28% compared to the sum of costs, if both operations had been done separately in two separate hospital stays at present Institution. Conclusion: Concurrent LC and IPOM is a safe, practical, and cost-effective procedure in carefully selected patients.